Estimating water input in the mining industry in Brazil: A methodological proposal in a data-scarce context. (March 2022) - Moura, Agnaldo; Lutter, Stephan; Siefert, Cesar Augusto Crovador; Netto, Nicolas Dombrowski; Nascimento, José Antônio Sena; Castro, Fernando
Highlights: For Brazil, we estimate spatially explicitly water inputs by the mining sector. Mine-specific water data is achieved juxtaposing several state and company sources. The methodology can be used as blueprint for other data-scarce countries. Mining water input is largest in the Brazilian North, central West, and southeast. Abstract: Metal mining plays a significant role in the Brazilian economy since its foundation as an overseas colony. The rapid increase in ore extraction brings along pressures on the country's water resources, as mining is a particularly water-intensive activity. However, site-specific data on water input and management are scarce. We propose a methodology for estimating water input in mining at a high geographical resolution. We focus on the three key metals mined in Brazil: iron, aluminum (i.e. bauxite ore), and copper, and derive water input coefficients for all mines from governmental and corporate sources as well as from the literature. We estimate that overall, the sum of the water inputs estimated for Brazilian bauxite, copper, and iron ore mining decreased by 15% from an average of 506.5±62.4 hm 3 in 2014 to an average of 408.4±67.2 hm 3 in 2017. The regions where most water was appropriated were Northern (Pará state) and Southeast (Minas Gerais) for iron, Northern (Pará) for aluminum, and Northern (Pará) and Central West (Goiás) for copper. We show that there are still significant consistency and data availability gaps, and that further work is still necessary to improve site-specific reporting and open access to data collected by public institutions.